KAPITAL SOSIAL IKATAN WARGA SANIANGBAKA - OKTAVIA S.Sos, M.Si, DIAN ANGGRAINI (STKIP PGRI Sumatera Barat, 2011)
Ties in the social structure and culture Saniangbaka society which denies its members have beenable to create a socio-economic forces in society as a whole Saniangbaka. The discussion in thisstudy focused on the Social Capital anchored in the social structure of Minangkabau society,namely in the form of organization Saniangbaka Residents in Jakarta. In discussing itinvestigated a). whether the social structure of Minangkabau culture influence the structure andorganization Saniangbaka Citizens Association (IWS) in Jakarta, b). whether the social structureand culture of Minangkabau and organizational structure will emerge capital di Jakarta IWSculturalcapital, c). and whether the cultural structures that emerged capital-capital culture.The study investigated using the framework of thinking about socio-cultural bonding structureSaniangbaka community about social capital as a value Mutual trust (trust) between members ofthe public against the leadership. Didefenisiakan Social Capital as a social institution involvingnetworks (Networks), norms (norms), and social trust (Social Trust) yangmendorong on a socialcollaboration (Coordination and cooperation) for the common good. (Putnam: 1993)Putnam (1993b: 3) also noticed that the social structure in the form of networks